A Novel Cytoplasmic Male Sterility in Brassica napus (inap CMS) with Carpelloid Stamens via Protoplast Fusion with Chinese Woad - Kang, Lei; Li, Pengfei; Wang, Aifan; Ge, Xianhong; Li, Zaiyun (Frontiers in Plant Science, 2017)
A novel cytoplasmic male sterility (CMS) in Brassica napus (inap CMS) was selected from the somatic hybrid with Isatis indigotica (Chinese woad) by recurrent backcrossing. The male sterility was caused by the conversion of tetradynamous stamens into carpelloid structures with stigmatoid tissues at their tips and ovule-like tissues in the margins, and the two shorter stamens into filaments without anthers. The feminized development of the stamens resulted in the complete lack of pollen grains, which was stable in different years and environment. The pistils of inap CMS displayed normal morphology and good seed-set after pollinated by B. napus. Histological sections showed that the developmental alteration of the stamens initiated at the stage of stamen primordium differentiation. AFLP analysis of the nuclear genomic composition with 23 pairs of selective primers detected no woad DNA bands in inap CMS. Twenty out of 25 mitochondrial genes originated from I. indigotica, except for cox2-2 which was the recombinant between cox2 from woad and cox2-2 from rapeseed. The novel cox2-2 was transcribed in flower buds of inap CMS weakly and comparatively with the fertile B. napus addition line Me harboring one particular woad chromosome. The restorers of other autoplasmic and alloplasmic CMS systems in rapeseed failed to restore the fertility of inap CMS and the screening of B. napus wide resources found no fertility restoration variety, showing its distinct origin and the related mechanism of sterility. The reasons for the mitochondrial rearrangements and the breeding of the restorer for the novel CMS system were discussed.